Triggering Mechanisms for Motor Actions: The Effects of Expectation on Reaction Times to Intense Acoustic Stimuli - Leow, L.; Uchida, A.; Egberts, J.; Riek, S.; Lipp, Ottmar; Tresilian, J.; Marinovic, Welber (Pergamon, 2018)
Motor actions can be released much sooner than normal when the go-signal is of very high intensity (>100 dBa). Although statistical evidence from individual studies has been mixed, it has been assumed that sternocleidomastoid (SCM) muscle activity could be used to distinguish between two neural circuits involved in movement triggering. We summarized meta-analytically the available evidence for this hypothesis, comparing the difference in premotor reaction time (RT) of actions where SCM activity was elicited (SCM+ trials) by loud acoustic stimuli against trials in which it was absent (SCM- trials). We found ten studies, all reporting comparisons between SCM+ and SCM- trials. Our mini meta-analysis showed that premotor RTs are faster in SCM+ than in SCM- trials, but the effect can be confounded by the variability of the foreperiods employed. We present experimental data showing that foreperiod predictability can induce differences in RT that would be of similar size to those attributed to the activation of different neurophysiological pathways to trigger prepared actions. We discuss plausible physiological mechanisms that would explain differences in premotor RTs between SCM+ and SCM- trials.